2016
DOI: 10.1515/jpm-2015-0399
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between markers of DNA and lipid oxidative damage in maternal and fetoplacental compartment in the mid-trimester of pregnancy

Abstract: Oxidative damage to lipids and DNA is also a part of physiologic processes during healthy pregnancy. 8-IP and 8-OHdG are constantly present in urine and AF. A weak positive correlation between maternal and fetal unit suggests a weak reflection of fetal oxidative status in maternal urine in the mid-trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These results were updated by Perlugi et al, where decreased levels of glutathione (GSH) were observed and significantly increased levels of several markers of oxidative stress were found in T21 amniotic fluid. The sources of oxidative stress in pregnancy can be various, from the placenta to maternal and fetal tissues, and the induction of oxidative stress reactions could also come from external factors [55].…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were updated by Perlugi et al, where decreased levels of glutathione (GSH) were observed and significantly increased levels of several markers of oxidative stress were found in T21 amniotic fluid. The sources of oxidative stress in pregnancy can be various, from the placenta to maternal and fetal tissues, and the induction of oxidative stress reactions could also come from external factors [55].…”
Section: Main Findingsmentioning
confidence: 99%
“…This would also indicate that the relationship between maternal and fetal oxidative stress is complex beyond a simple diffusion. The source of oxidative stress in pregnancy manifests in the placenta, in particular, but also originates from maternal and/or fetal cells and external factors [55]. It can be hypothesized that the correlation is described by some monotonic, but not linear function.…”
Section: Main Findingsmentioning
confidence: 99%
“…The OS biomarkers can be found not only in blood but also in placenta [25], amniotic fluid [26], cord plasma [27,28], and urine [17]. A modern diagnostic approach is to offer less invasive or even noninvasive tests for a diagnosis of different pathologies, and saliva seems to be a suitable material.…”
Section: Introductionmentioning
confidence: 99%